Wind-Driven Processes Controlling Oceanic Heat Delivery to the Amundsen Sea, Antarctica - Dotto, Tiago S.; Naveira Garabato, Alberto C.; Bacon, Sheldon; Holland, Paul R.; Kimura, Satoshi; Firing, Yvonne L.; Tsamados, Michel; Wåhlin, Anna K.; Jenkins, Adrian (Journal of Physical Oceanography, 2019)
Variability in the heat delivery by Circumpolar Deep Water (CDW) is responsible for modulating the basal melting of the Amundsen Sea ice shelves. However, the mechanisms controlling the CDW inflow to the region’s continental shelf remain little understood. Here, a high-resolution regional model is used to assess the processes governing heat delivery to the Amundsen Sea. The key mechanisms are identified by decomposing CDW temperature variability into two components associated with 1) changes in the depth of isopycnals [heave (HVE)], and 2) changes in the temperature of isopycnals [water mass property changes (WMP)]. In the Dotson–Getz trough, CDW temperature variability is primarily associated with WMP. The deeper thermocline and shallower shelf break hinder CDW access to that trough, and CDW inflow is regulated by the uplift of isopycnals at the shelf break—which is itself controlled by wind-driven variations in the speed of an undercurrent flowing eastward along the continental slope. In contrast, CDW temperature variability in the Pine Island–Thwaites trough is mainly linked to HVE. The shallower thermocline and deeper shelf break there permit CDW to persistently access the continental shelf. CDW temperature in the area responds to wind-driven modulation of the water mass on-shelf volume by changes in the rate of inflow across the shelf break and in Ekman pumping-induced vertical displacement of isopycnals within the shelf. The western and eastern Amundsen Sea thus represent distinct regimes, in which wind forcing governs CDW-mediated heat delivery via different dynamics.